Premenstrual syndrome as a possible presymtomatic marker for negative outcomes of pregnancy - E. Eros (European Psychiatry, 2022)
Introduction Hungarian Family Planning Service’s mission is decreasing the negative outcomes of pregnancy, including perinatal depression.